Living conditions and receptive vocabulary of children aged two to five years Condições de vida e vocabulário receptivo em crianças de dois a cinco anos - Carmen Sílvia Basílio; Rosana Fiorini Puccini; Edina Mariko Koga da Silva; Márcia Regina Marcondes Pedromônico (Universidade de São Paulo, 2005)
OBJECTIVE: To assess the receptive vocabulary of children aged between two years and six months and five years and eleven months who were attending childcare centers and kindergarten schools. METHODS: An analytical cross-sectional study was carried out in the municipality of Embu, Southeastern Brazil. The Peabody Picture Vocabulary Test and analysis of factors associated with children's performance were applied. The sample consisted of 201 children of both genders, aged between two and six years. Statistical analysis was performed using multivariate analysis and logistic regression model. The dependent variable analyzed was test performance and the independent variables were child's age, mother's level of education and family socio-demographic characteristics. RESULTS: It was observed that 44.3% of the children had performances in the test that were below what would be expected for their age. The factors associated with the best performances in the test were child's age (OR=2.4; 95% CI: 1.6-3.5) and mother's education level (OR= 3.2; 95% CI: 1.3-7.4). CONCLUSIONS: Mother's education level is important for child's language development. Settings such as childcare and kindergarten schools are protective factors for child development in families of low income and education. OBJETIVO: Avaliar o vocabulário receptivo de crianças de dois anos e seis meses a cinco anos e 11 meses que freqüentam creches e pré-escolas. MÉTODOS: Estudo transversal e analítico realizado no município de Embu, Estado de São Paulo. Utilizou-se o Teste de Vocabulário por Imagem Peabody e análise de fatores associados ao desempenho. A amostra foi constituída de 201 crianças de ambos os sexos, com idade entre dois e seis anos. Foram realizados análise multivariada e modelo de regressão logística. A variável dependente analisada foi o desempenho no teste e as variáveis independentes foram a idade da criança, tempo de escolaridade e série, e características sociodemográficas de suas famílias. RESULTADOS: Observou-se que 44,3% das crianças apresentaram desempenho inferior ao esperado para a idade no teste e os fatores associados ao melhor desempenho foram a idade da criança (OR=2,4; IC 95%: 1,6-3,5) e a escolaridade materna (OR=3,2; IC 95%: 1,3-7,4). CONCLUSÕES: A escolaridade maternal é importante no desenvolvimento de linguagem da criança. As instituições como creches e pré- escolas são fatores de proteção do desenvolvimento infantil em famílias de baixa renda e com baixa escolaridade.